ChemInform Abstract: Synthesis of Fluorenone and Anthraquinone Derivatives from Aryl‐ and Aroyl‐Substituted Propiolates. Issue 6 (11th February 2014) - Puenner, Florian; Schieven, Justin; Hilt, Gerhard
Abstract Compound (VIIc) is only obtained in traces contaminated with compound (XII).